1990
DOI: 10.1039/c39900001665
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular hetero Diels–Alder reaction of 1-thiabutadienes, 1-aryl-3-[2-(alkenyloxy)phenyl]propene-1-thiones and 2-[2-(alkenyloxy)benzylidene]-3,4-dihydronaphthalene-1(2H)-thiones

Abstract: a,P-Unsaturated thioketones 4 , 5 and 9, which are formed in situ by thionation of the corresonding ketones, undergo intramolecular hetero Diels-Alder reactions with high regio-and diastereo-selectivities (transkis) to give dihydrothiopyran-fused cycloadducts 6, 7 and 10.Intramolecular Diels-Alder reactions provide useful methods cedures However, IHDA reactions involving a thiofor construction of polycyclic systems, and have been widely carbonyl function have received little attention so far, applied in organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Reaction of α,β-unsaturated ketone 14 with P 4 S 10 in CS 2 gave an intramolecular Diels−Alder reaction to yield the cyclo adduct 16 , possibly through the thione intermediate 15 (Scheme ) …”
Section: Reactions Of P4s10mentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction of α,β-unsaturated ketone 14 with P 4 S 10 in CS 2 gave an intramolecular Diels−Alder reaction to yield the cyclo adduct 16 , possibly through the thione intermediate 15 (Scheme ) …”
Section: Reactions Of P4s10mentioning
confidence: 99%
“…Reaction of R,β-unsaturated ketone 14 with P 4 S 10 in CS 2 gave an intramolecular Diels-Alder reaction to yield the cyclo adduct 16, possibly through the thione intermediate 15 (Scheme 6). 74 Treatment of the diketone 17, having an R,β-unsaturated unit with P 4 S 10 in pyridine (dry), for 3-5 h at room temperature resulted in the formation of thiopyran ring 18 (Scheme 7). 75 On the other hand, it was reported that the treatment of the same ketone with P 4 S 10 in refluxing xylene yielded trithiapentalene 19.…”
Section: Ketonesmentioning
confidence: 99%